Overview of Computer Networks for Data Transmission at Pondok Kopi Islamic Hospital, Jakarta, Indonesia - Muhammad Caisar Ramadhan; Adi Widodo; Daniel Happy Putra; Noviandi (Natural Sciences Engineering and Technology Journal, 2023)
Network quality monitoring can provide services in the provision of computer network performance in the provision of data transmission according to the level of aspects related to the performance of network infrastructure systems and the number of clients operating for each computer. During the day, at certain hours, many subscribers use the network when the connection is blocked, and the graphics on the screen reach their highest levels. By monitoring computer network installation graphics, Axence netTools software needs to know bandwidth management to overcome network congestion by analyzing the QoS (quality of service) of computer network data transmission. The purpose of this study is to provide quality of service presentation material on LAN infrastructure performance using the TIPHON standard to measure LAN performance and analyze the factors that influence the results of quality of service measurements and obtain packet loss, delay, jitter based on class classification and average bandwidth value, according to TIPHON. The research method used is observation, interviews, literature study, monitoring, and qualitative descriptive research methods. The results showed that the percentage value of quality of service based on the TIPHON standardization was 66.66%. This result was classified as "unsatisfactory" because the average packet loss was 40%. The average percentage of delay is 115ms, and the average percentage of jitter is 7.5ms. The factors that affect the QoS index results are the distance of computer network transmission facilities and the need to monitor computer networks when adding and maximizing bandwidth according to TIPHON standards.